2023
DOI: 10.1111/ropr.12544
|View full text |Cite
|
Sign up to set email alerts
|

Net‐zero carbon declarations by Japanese local governments: What caused the domino‐like diffusion?

Abstract: Sub‐national governments are a crucial non‐state actor for mitigating climate change. This importance has recently strengthened as increasing numbers of municipalities declare net‐zero carbon emission goals to support the Paris Agreement, often well ahead of national governments. In Japan, net‐zero declarations have also diffused widely, with nearly 800 declarations appearing in domino‐like fashion over 2019–2022. To elucidate the factors that propelled this rapid diffusion, we used an event‐history analysis b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The findings in this issue show that local communities are actively involved in climate change mitigation under certain circumstances. For example, Nakazawa et al (2023) show that in Japan between 2019 and 2022 net‐zero declarations rapidly diffused across subnational governments. In the beginning, this development was triggered by factors related to the subnational entity, for example, the participation in transnational city networks, endowed human and financial resources, or political leadership.…”
Section: Drivers Of Local‐level Climate Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this issue show that local communities are actively involved in climate change mitigation under certain circumstances. For example, Nakazawa et al (2023) show that in Japan between 2019 and 2022 net‐zero declarations rapidly diffused across subnational governments. In the beginning, this development was triggered by factors related to the subnational entity, for example, the participation in transnational city networks, endowed human and financial resources, or political leadership.…”
Section: Drivers Of Local‐level Climate Policiesmentioning
confidence: 99%
“…The third cluster of frameworks deals with the context of the cities – that is often used in a comparative perspective. With a focus on network effects between the cities and regions, the empirical study by Nakazawa et al (2023) contributes to the literature on policy diffusion (see e.g., Berry & Berry, 2018). Kern et al (2023) draw in their work on the matching cities and scaling approach (see e.g., Kern et al, 2023; van der Heijden, 2022).…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…Vertical integration is measured by asking whether SAC members are recruited from diverse sectors. It is repeatedly observed that in the climate policy domain the interests and worldviews are particularly different between economic sectors and environmental groups [23,24], but also between national and local governments [25], and scientists and non-scientists [8]. Securing the chances for actors from various sectors to speak out and listen to others in the SACs is a necessary condition for enhancing EPI.…”
Section: Measurement Of Vertical and Horizontal Integrationmentioning
confidence: 99%